Avanço do desmatamento e transformações socioespaciais no sul amazonense - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Amazonas is a state that has been suffering annually from the problem of deforestation, in 2016 the deforestation rate increased by 24.6% in the entire legal Amazon. Unlike other years, today deforestation in the state is linked to livestock activity that occupies more than 70% of the Amazonian territory, which is also the reason for burning, in the present research we investigate the municipalities of Apuí, Boca do Acre and Lábrea, which are the municipalities that most deforest for livestock and grain planting in the Amazon and, also, members of what we call the arc of deforestation. The world's concern with the deforestation of forests, in particular with the deforestation of the Amazon rainforest, is nothing new. This concern rests on studies that demonstrate, among other aspects, its importance for global climate balance and stability, for the provision of environmental services, due to its enormous biodiversity and socio-diversity. However, despite this recognition, regarding the Amazon Forest, deforestation and fires have not ceased, on the contrary, despite a series of national and sometimes international institutional measures, they continue to happen in an unregulated way. Deforestation rates in the Legal Amazon have been increasing since 1990 (INPE, 2019). And although the forest is deforested for numerous reasons, illegal logging and cattle ranching are still the predominant causes. From the year 2000, the expansion of soy and livestock gained prominence in the advance of the agricultural frontier in the Legal Amazon due to the international demand for meat and soy, where Brazil is among the main suppliers of these commodities (DOMINGUES, 2012). The advances of these fronts coming from the north of Mato Grosso and Rondônia, in addition to the west of Pará, put pressure on the south of Amazonas, especially at the junction of the BR-364 and BR-230, where the municipalities of Apuí, Boca do Acre and Labrea. Over the last 15 years, strategies to contain the advance of deforestation have included measures ranging from repression through licensing procedures, monitoring and fines. However, as we can see, such measures did not have the desired effect. Among others, reasons for the actions of the State itself that stimulated the installation of infrastructure, subsidized credits, appreciation of foreign currency and the recent loosening both in inspection and in the Forestry Code (BRASIL, 2012). Given this scenario, the concern of this research is to understand which processes and ongoing dynamics contribute to the increase in deforestation rates in the mesoregion of the South Amazon region. In principle, the hypothesis is that deforestation is associated with the expansion of livestock, but are there other factors and variables associated with this expansion? Who are the actors and economic and political agents associated with deforestation processes in this mesoregion? How does this deforestation and the advance of agroindustry affect small producers? Where are the conflicts caused by this environmental degradation concentrated? These are the guiding questions of this research.
Keywords: .; .; .; CIENCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA HUMANA; Desmatamento; Corte raso; Sul-amazonense; Amazônia